2020
DOI: 10.1002/jssc.201901067
|View full text |Cite
|
Sign up to set email alerts
|

Field‐amplified sample injection combined with CE for the enantiodetermination of cathinones in urine samples

Abstract: This work presents a capillary electrophoresis methodology for the enantiodetermination of cathinones in urine employing a liquid–liquid extraction sample pretreatment. The cathinones were enantioseparated by adding a mixture of 8 mM 2‐hydroxypropyl β‐cyclodextrin and 5 mM β‐cyclodextrin to the background electrolyte, which consists of 70 mM of monosodium phosphate aqueous solution at pH 2.5. Field‐amplified sample injection was used as preconcentration strategy to improve the sensitivity. We studied various p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In the field-amplified stacking injection (FASI) technique, more efficient sample enrichments can be generally attained by electrokinetically injecting a low-conductivity sample solution. From the year 2019 to 2021, FASI has been applied to the analyses of macrocyclic antibiotics [22], diltiazem and metoprolol tartrate [23], cold medicine compounds [24], corticosteroids [25], α-blockers [26], 2,2'-azobis(2-amidinopropane) ion [27], sulfonamides [28], chlorophenols [29], cathinones [30], 9-hydroxyrisperidone [31], linear alkylbenzene sulfonates [32], quetiapine and its metabolites [33] as summarized in Table 2. Kowalski et al reported an FASI method for stacking macrocyclic antibiotics in hydrophobic interaction electrokinetic chromatography [22].…”
Section: Application Of Field-amplified Sample Stackingmentioning
confidence: 99%
“…In the field-amplified stacking injection (FASI) technique, more efficient sample enrichments can be generally attained by electrokinetically injecting a low-conductivity sample solution. From the year 2019 to 2021, FASI has been applied to the analyses of macrocyclic antibiotics [22], diltiazem and metoprolol tartrate [23], cold medicine compounds [24], corticosteroids [25], α-blockers [26], 2,2'-azobis(2-amidinopropane) ion [27], sulfonamides [28], chlorophenols [29], cathinones [30], 9-hydroxyrisperidone [31], linear alkylbenzene sulfonates [32], quetiapine and its metabolites [33] as summarized in Table 2. Kowalski et al reported an FASI method for stacking macrocyclic antibiotics in hydrophobic interaction electrokinetic chromatography [22].…”
Section: Application Of Field-amplified Sample Stackingmentioning
confidence: 99%
“…Offline preconcentration requires pretreatment of the target analyte, which is characterized by large reagent consumption and a cumbersome operation process. On-line preconcentration techniques include ITP [23,24], field amplified sample stacking [25][26][27], large volume sample stacking [28][29][30], field amplified sample injection [31,32], sweeping techniques [33,34], pH junction techniques [35], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, several publications referenced CE for the enantiomeric separation of SC using cyclodextrines as chiral selector [10][11][12][13][14][15]. Recently, several preconcentration strategies were evaluated in order to reach high sensitivity for the enantiodetermination of cathinones in urine samples [16,17]. This research group also proposed an in-line SPE with CE-MS analysis for the enantiodetermination of R,S-3,4-methylenedioxypyrovalerone [18].…”
Section: Introductionmentioning
confidence: 99%